Upregulation of inflammatory gene transcripts in periosteum of chronic migraineurs: Implications for extracranial origin of headache. Issue 6 (5th May 2016) - Perry, Carlton J.; Blake, Pamela; Buettner, Catherine; Papavassiliou, Efstathios; Schain, Aaron J.; Bhasin, Manoj K.; Burstein, Rami
Abstract : Objective: Chronic migraine (CM) is often associated with chronic tenderness of pericranial muscles. A distinct increase in muscle tenderness prior to onset of occipital headache that eventually progresses into a full‐blown migraine attack is common. This experience raises the possibility that some CM attacks originate outside the cranium. The objective of this study was to determine whether there are extracranial pathophysiologies in these headaches. Methods: We biopsied and measured the expression of gene transcripts (mRNA) encoding proteins that play roles in immune and inflammatory responses in affected (ie, where the head hurts) calvarial periosteum of (1) patients whose CMs are associated with muscle tenderness and (2) patients with no history of headache. Results: Expression of proinflammatory genes (eg, CCL8, TLR2 ) in the calvarial periosteum significantly increased in CM patients attesting to muscle tenderness, whereas expression of genes that suppress inflammation and immune cell differentiation (eg, IL10RA, CSF1R ) decreased. Interpretation: Because the upregulated genes were linked to activation of white blood cells, production of cytokines, and inhibition of NF‐κB, and the downregulated genes were linked to prevention of macrophage activation and cell lysis, we suggest that the molecular environment surrounding periosteal pain fibers is inflamed and in turn activates trigeminovascular nociceptors that reach the affected periosteum through suture branches of intracranial meningeal nociceptors and/or somatic branches of the occipital nerve. This study provides the first set of evidence for localized extracranial pathophysiology in CM. Ann Neurol 2016;79:1000–1013